Interconnection Family Education and Social Education Toward Social Harmony in the Interfaith Society - Zaim, Zaimudin (Sosio-Didaktika: Social Science Education Journal, 2023)
This research aims to prove the importance of the interconnection between family education and social education to build social harmony in interfaith communities. The research method used is a survey using a structured questionnaire as a data collection instrument. Data collection was carried out through observation, interviews and documentation. The data collected is qualitative data in the form of social phenomena in the form of education carried out by families and communities in an integrated manner. The research results show that there is a continuous interconnection between family education and social education in building harmony between religious communities. Families and communities work collaboratively to provide education to form an attitude of tolerance towards other religious groups. The conclusion of this research is that the interconnection of family education and social education is an important factor in building harmony between religious believers. Therefore, in an effort to promote inter-religious harmony in society, it is important to strengthen the interconnection between family education and social education.